2019
DOI: 10.1080/15389588.2018.1527032
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and marijuana use among young injured drivers in Arizona, 2008–2014

Abstract: Objective: We examined alcohol and marijuana use among injured drivers aged 16-20 years evaluated at Arizona level 1 trauma centers during 2008-2014. Methods: Using data from the Arizona State Trauma Registry, we conducted a descriptive analysis of blood alcohol concentration (BAC) and qualitative test results (positive or negative) for delta-9-tetrahydrocannabinol (THC) by year of age, sex, race, ethnicity, injury severity, seat belt use, motorcycle helmet use, and type of vehicle driven. To explore compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 21 publications
(24 reference statements)
0
7
0
1
Order By: Relevance
“…The second highest was among the youngest drivers (those aged 16–20 years), who already have a heightened crash risk because of inexperience ¶ ; thus, their substance use is of special concern. In a study of injured drivers aged 16–20 years evaluated at level 1 trauma centers in Arizona during 2008–2014 ( 3 ), 10% of tested drivers were simultaneously positive for both alcohol and tetrahydrocannabinol, the main psychoactive component of marijuana. Data from the 2018 NSDUH indicate a high prevalence (34.8%) of past-year marijuana use among young adults aged 18–25 years ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The second highest was among the youngest drivers (those aged 16–20 years), who already have a heightened crash risk because of inexperience ¶ ; thus, their substance use is of special concern. In a study of injured drivers aged 16–20 years evaluated at level 1 trauma centers in Arizona during 2008–2014 ( 3 ), 10% of tested drivers were simultaneously positive for both alcohol and tetrahydrocannabinol, the main psychoactive component of marijuana. Data from the 2018 NSDUH indicate a high prevalence (34.8%) of past-year marijuana use among young adults aged 18–25 years ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of these cases, risk behaviors have been found, such as using cell phones and not wearing crash helmets when riding a motorcycle. [11][12][13] Among university students who drove motorcycles in Vietnam in 2016, the most prevalent risk behaviors found were using cells phones while driving, driving on footpaths, speeding, driving on the wrong side of the road, not wearing a crash helmet and drinking alcohol. 11 In the state of Arizona, United States, between 2008 and 2014, analysis of alcohol and cannabis consumption among young vehicle drives involved in accidents showed that in that state they were more prone to not wearing crash helmets and suffering more severe injuries.…”
Section: Discussionmentioning
confidence: 99%
“…11 In the state of Arizona, United States, between 2008 and 2014, analysis of alcohol and cannabis consumption among young vehicle drives involved in accidents showed that in that state they were more prone to not wearing crash helmets and suffering more severe injuries. 12 With regard to the activities of motorcycle couriers, other vulnerability factors can be frequently observed, related to work conditions with long working hours that contribute to distraction and tiredness, 14 in addition to the pressure to deliver goods and transport people rapidly, which is capable of favoring negligence and lack of safe attitudes. Greater exposure of these individuals to risk behavior may be influenced by cultural issues, in addition to employability status: whereas the unemployed may take on risk behaviors due to anxiety, stress and depression, those who are employed tend to be more impatient and not obey the highway code, breaking speed limits when they are late for work and pressured to increase productivity.…”
Section: Discussionmentioning
confidence: 99%
“…21 One study examining the rates of simultaneous alcohol/ cannabis use among underaged injured drivers in Arizona found that 32% of drivers who were tested for both substances had alcohol and cannabis positive tests. 22 Another study found that high school seniors who reported simultaneous alcohol/cannabis use had higher rates of traffic violations and motor vehicle crashes than individuals who used either substance individually. 23 In addition, simulation driving studies show that low amounts of either alcohol or cannabis can potentiate the effect of the other substance.…”
Section: Introductionmentioning
confidence: 99%